Implementasi Pengelolaan Bisnis Hotel Syariah Pada Hotel RedDoorz Syariah Medan - Sembiring, Marlena Br; Amalia, Alfi (Journal of Student Development Informatics Management (JoSDIM), 2023)
This thesis is a discussion that aims to find out. 1. How to implement Standard Operating Procedures (SOP) in accordance with sharia at the Red Doorz Syariah Medan Teladan Hotel. 2. What is the quality of sharia service for guests at the Red Doorz Syariah Medan Teladan Hotel. 3. How is management implemented at the Red Doorz Syariah Medan Teladan Hotel. The research instruments used were observation guidelines and interviews. The data analysis techniques used are data reduction, data presentation and data verification. The results of the research can be summarized as follows: 1. Implementation of SOPs in accordance with sharia at the Reddorz Teladan Syariah Hotel in Medan where sharia principles need to be considered in every product offered to hotel guests which must be useful and in accordance with Islamic rules, the application of standard operational procedures is in accordance with the reference from DSN-MUI. 2. Quality of sharia service for guests at the RedDoorz Syariah Hotel Medan Teladan Hotel Reddorz Syariah Teladan Medan in terms of service, by implementing the 3 elements (front office, housekeeping, food and drink, restaurant), the hotel management assumes that it has implemented basic services that every visitor needs for sharia hotel accommodation. 3. Implementation of Exemplary RedDoorz Syariah Medan Hotel Business Management, where the RedDoorz Syariah Medan Hotel management system has been implemented in accordance with Islamic sharia, namely having and using a halal guarantee system, Reddoorz Syariah Hotel Medan has implemented sharia principles in accordance with DSN-MUI guidelines, including: screening of guests who come, does not provide alcohol or alcohol, the products provided by the hotel are halal products, does not provide an entertainment area, has a prayer room and place for ablution, has provided worship equipment in each room, which means this hotel has implemented sharia principles. However, the implementation of the Reddorz Syariah Hotel Teladan Medan still has many shortcomings, where the Reddorz Syariah Hotel Teladan Medan does not collaborate with sharia financial institutions, does not have a certificate from the MUI institution, there is no sharia supervisory board that guarantees that the products provided by the Hotel Reddorz Syariah Teladan Medan guaranteed halal.